Impact of IIP & Inflation on S&P BSE 500 Listed Companies : An Analysis of Granger Causality - Srivastava, Himadri; Chauhan, Swati; Singh, Paramjeet (Indian Journal of Research in Capital Markets, 2019)
The objective of this study was to analyze the impact of macroeconomic variables on functioning of the Indian stock market. Financial markets play a very important role in the growth and development of an economy. Economy is affected by various macro and microeconomic variables. Recently, demonetization and the new indirect tax system, that is, GST have brought a lot of changes in the economy and have affected the functioning of the stock market. Various studies have shown this relationship by applying various financial models. In this study, monthly data of macroeconomic variables like inflation and index of industrial production on BSE 500 companies for the period from 2011–12 to 2017–18 were taken. The study used Augmented Dickey-Fuller (ADF) test for unit root test; multiple regression and Granger causality test were also applied to find the results. Time series data must be stationary, otherwise the results are not useful. To make the data stationary, ADF was used. Multiple regression was used to find the significant variables and Granger causality was used to check the causality between the significant variables. The study found that both macroeconomic variables had a significant relationship with BSE 500 listed companies.